ANTROPOLOGICAL SKETCH OF THE SOCIAL STRUCTURE OF TRANSITIONAL SOCIETY - I. M. Bondarevych; N. M. Dievochkina (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to create a working model of the social structure of a society with transition type, which moves from its totalitarian past to democratic organization. In our model the basis of social stratification is the principle of the influence of individuals’ personal characteristics on social transformations. As such principle, we propose self-control of mental content. Theoretical basis. The object of the research is a transitional society. The subject of the research is its social stratification. The individual mental content determines not only his behavior, but a life strategy that affects the social development of society as well. We determined the social structure layers according to the degree of the individual’s self-control of mental content. Carriers of slave consciousness have the lowest degree of control, which are in a fanatical state from the surrounding psychosocial influences (ideology, religion, etc.). The insignificant degree of self-control is discovered among those who have seized consciousness - social infants susceptible to populist promises. The social layer of the owners of injured consciousness (egoists and nihilists) demonstrates the highest degree of self-awareness among these three social layers. All three social layers, taking into account their life strategies, which are conditioned with the prevailing external influence on their consciousness, belong to the zone of social deformation. The last one is the core of the social structure of the transitional society. The halo of the structure of such society forms a social layer of socially sensitive personalities. Since they build their own strategy of their own lives more independently, it can be assumed that they are conventionally out of the social deformation zone. Originality. The proposed model of the social structure of a transitional society has excellent prognostic capabilities. Social forecasts are based on a comparative analysis of the quantitative ratio of all social layers. For example, the prevailing aggregate number of slave consciousness carriers and owners of the seized consciousness is characteristic for the first steps of a post-totalitarian society. If it continues to be fixed in time, this is the evidence of the inhibition process in social transformations and so on. Conclusions. The dynamics of social perturbations in transitional societies is effectively investigated due to the lines of the greatest mutual influence of personal characteristics on social processes. One of these lines is the individual’s self-control in sphere of the mental content. The social structure model of a particular transition society created by the results of future sociological researches will allow to predict the state and prospects of its social transformations. And the main thing is that it will help to detect the factors of the success in social development of a particular society, which is the indispensable condition for the construction of a state policy.